Role of nitric oxide in the regulation of digital pulse volume amplitude in humans - Nohria, Anju; Gerhard-Herman, Marie; Creager, Mark A; Hurley, Shauna; Mitra, Debi; Ganz, Peter (Journal of applied physiology (1985), 2006)
Cardiovascular Division, Brigham and Women's Hospital, Boston, Massachusetts Submitted 6 October 2005 ; accepted in final form 11 April 2006 Measurement of the increase in digital pulse volume amplitude (PVA) during reactive hyperemia relative to baseline (PVA-RH) is being applied widely as a convenient test of nitric oxide bioavailability. However, evidence linking digital PVA-RH to nitric oxide is currently lacking. Accordingly, we investigated whether nitric oxide is responsible for the increase in digital PVA. During reactive hyperemia, we used a peripheral arterial tonometer to record digital PVA at baseline and during reactive hyperemia. The role of nitric oxide in these responses was investigated in 19 healthy subjects by inhibiting nitric oxide synthesis with N G -nitro- L -arginine methyl ester ( L -NAME). Ten subjects underwent the identical protocol with saline and five with phenylephrine, a nonspecific vasoconstrictor, instead of L -NAME. The change in digital PVA after drug administration was compared between the three groups. Relative to the response with saline (5 ± 2%), baseline PVA was unchanged by L -NAME infusion (10 ± 2%), but it decreased significantly with phenylephrine (50 ± 12%; P = 0.003). PVA-RH increased slightly with saline infusion (9 ± 4%). In comparison, PVA-RH was significantly blunted by L -NAME administration (46 ± 21%; P = 0.002) and was relatively unchanged by phenylephrine (20 ± 9%). The present study establishes a central role for nitric oxide in the augmentation of PVA during reactive hyperemia. The measurement of digital PVA-RH may indeed provide a simple means of assessing endothelial function in humans. endothelium; vasodilation; reactive hyperemia Address for reprint requests and other correspondence: A. Nohria, Cardiovascular Div., Brigham and Women's Hospital, 75 Francis St., Boston, MA 02115 (e-mail: anohriaatpartners.org )